Ash-shidq Linamudzaj Al-maaddah Al-nachwiyyah Al- ittishaliyyah Lithullab Qism Al-lughah Al-arabiyyah Fii Al-jaami’ah Al-islaamiyyah (Universitas Negeri Semarang, 2023)
Abstract: This research aims to test the validity of the learning material model for Arabic grammar using the communicative approach for the students of Arabic Departement at the State Islamic Universities in Indonesia. The learning material model for Arabic grammar is prepared using a communicative approach to provide students with basic grammatical rules that help them understand and communicate Arabic texts. The data sources are five experts who assess the validity of learning material model. Validity data is collected through a questionnaire. Data in the form of expert assessment of the model were analyzed quantitatively descriptively, while data in the form of suggestions for revision of the model were analyzed qualitatively. The results of the research show that the average validity score of the learning material model for Arabic grammar is 3.33 in very good category. It means that the learning materials model is valid for use with little revision in some aspects, namely the content, design, writing, colouring, and layout